Plasmodium falciparum parasites exit the infected erythrocyte after haemolysis with saponin and streptolysin O - Quadt, Katharina; Smyrnakou, Xanthoula; Frischknecht, Friedrich; Böse, Guido; Ganter, Markus (Parasitology research, 2020)
Malaria is caused by unicellular parasites of the genus Plasmodium, which reside in erythrocytes during the clinically relevant stage of infection. To separate parasite from host cell material, haemolytic agents such as saponin are widely used. Previous electron microscopy studies on saponin-treated parasites reported both, parasites enclosed by the erythrocyte membrane and liberated from the host cell. These ambiguous reports prompted us to investigate haemolysis by live-cell time-lapse microscopy. Using either saponin or streptolysin O to lyse Plasmodium falciparum-infected erythrocytes, we found that ring-stage parasites efficiently exit the erythrocyte upon haemolysis. For late-stage parasites, we found that only approximately half were freed, supporting the previous electron microscopy studies. Immunofluorescence imaging indicated that freed parasites were surrounded by the parasitophorous vacuolar membrane. These results may be of interest for future work using haemolytic agents to enrich for parasite material.
Gesehen am 21.08.2024